Prevalence of Healthy Eating Initiatives in Australian Primary Schools: A Cross‐Sectional Survey - Jessica Bell; Kate M. O'Brien; Luke Wolfenden; Sze Lin Yoong; Adrian Bauman; Lucy Leigh; Christophe Lecathelinais; Rebecca K. Hodder (Health Promotion Journal of Australia, 2026)
ABSTRACT Issue Addressed Schools are recommended settings for promoting healthy eating, but to achieve population‐level impact, initiatives must be widely implemented. Limited data are available to assess the implementation of Australian school‐based healthy eating initiatives. This study examined the implementation of healthy eating initiatives in Australian primary schools and whether implementation is associated with school characteristics (school size, remoteness, socio‐economic status). Methods A cross‐sectional study surveyed a nationally representative sample of Australian primary school principals (August 2022–October 2023) regarding 32 healthy eating initiatives across five opportunities for healthy eating: healthy food in the classroom, at school, brought to school, outside of school and other. Initiatives were identified from recent systematic reviews aligned with Australian and global guidelines. Prevalence estimates were weighted to the national school population, and logistic regression models examined associations with school characteristics. Results Of the 669 participating schools, 569 completed the healthy eating survey, with implementation rates ranging from 7% to 97%. The most frequently implemented initiatives were: in the classroom, ‘Permission or breaks to drink water in class time in ≥ 80% of classes daily’ (97%); at school, ‘Install water stations for free access to cooled plain or optionally carbonated water’ (64%); brought to school, ‘Information on healthy eating sent home to parents’ (88%); and outside of school, ‘Healthy eating programs delivered in partnership with community organisations or services’ (31%). Ten initiatives were associated with school size ( n = 5), remoteness ( n = 7), or socio‐economic status ( n = 3). Conclusions Implementation rates of the 32 healthy eating initiatives varied substantially, and most initiatives had similar rates across school characteristics (school size, remoteness, socio‐economic status). So What? This first national study provides crucial information on the implementation of individual healthy eating initiatives in Australian primary schools, highlighting which initiatives and school subgroups require policy and practice investment to support implementation.